Regulation of metabolic shifts in Clostridium acetobutylicum ATCC 824 - Girbala, Laurence (2011)
Alcohol formation was initiated in continuous cultures of Clostridium acetobutylicum under distinct steady-state conditions: (i) in glucose-limited cultures established at low operating pH with formation of butanol, ethanol and acetone (induction of the solventogenesis) in which cells contained normal levels of NADH and a high level of ATP and butyric acid; and (ii) by increasing the NADH pressure at neutral pH in glucose-limited cultures after addition of Neutral red, or in glucose-glycerol or glucose-glycerol-pyruvate grown cultures, with a strictly alcohologenic metabolism (no acetone produced) associated with high levels of intracellular NADH and various levels of ATP. These two different metabolic shift systems are correlated with the expression of different genes involved in the solvent-forming pathways and the electron flow distribution. A high NADH level leading to butanol and ethanol formation was accompanied by increased activities of the NADH-dependent alcohol and butyraldehyde dehydrogenases, and ferredoxin:NAD(P)+ reductases, and by decreased activities of the NADH:ferredoxin reductase. This last group of enzymes constitutes the key enzymes regulating electron flow, since no change in hydrogenase activity was observed. On the other hand, classical solventogenesis appears to be characterized by high levels of expression of the NADPH-dependent alcohol and butyraldehyde dehydrogenases, and of the two enzymes involved in the acetone-forming pathway, while the ferredoxin:NAD(P)+ reductases were not synthesized. A decrease of the in vitro hydrogenase activity explains the lower hydrogen generation. In addition, the regulation of the intracellular pH was different between the alcohologenic culture grown at neutral pH and the solventogenic cultures grown at low pH. An inversion of the transmembrane pH gradient was observed during the production of alcohol at neutral pH and was related to a lower in vivo specific rate of hydrogen production while in the cultures grown at low pH the transmembrane pH generation was not linked to the F1F0 ATPase activity.